2009
DOI: 10.3892/ijo_00000262
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy on anaplastic thyroid carcinoma of valproic acid alone or in combination with doxorubicin, a synthetic chenodeoxycholic acid derivative, or lactacystin

Abstract: Abstract. The present study investigated the mechanism underlying the antitumor activity of the histone deacetylases inhibitor valproic acid (VPA), alone and in combination with doxorubicin, a synthetic chenodeoxycholic acid derivative (HS-1200), or the proteasome inhibitor lactacystin on cultured anaplastic thyroid carcinoma KAT-18 cells. Cell viability was evaluated by trypan-blue exclusion. Western blotting determined caspase and histone deacetylase activities and expression of poly(ADP)-ribose polymerase. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Although DOX, as well as sorafenib, were shown to cause cell death, partially by enhancing apoptosis in HCC cells [ 6 , 7 , 51 ], the exact mechanism underlying the pharmacological synergy has not yet been determined. Moreover, VPA was reported to sensitize anaplastic thyroid carcinoma (ATC) cells to DOX, which caused apoptosis via the induction of histone hyperacetylation or apoptosis-related gene expression [ 52 , 53 , 54 ]. Concurrently, several studies demonstrated that VPA showed synergistic effects with well-known anticancer drugs, such as aspirin, flavopiridol, mitomycin C, cisplatin, adriamycin, and DOX, and could induce cell death in various cancer cells [ 24 , 52 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although DOX, as well as sorafenib, were shown to cause cell death, partially by enhancing apoptosis in HCC cells [ 6 , 7 , 51 ], the exact mechanism underlying the pharmacological synergy has not yet been determined. Moreover, VPA was reported to sensitize anaplastic thyroid carcinoma (ATC) cells to DOX, which caused apoptosis via the induction of histone hyperacetylation or apoptosis-related gene expression [ 52 , 53 , 54 ]. Concurrently, several studies demonstrated that VPA showed synergistic effects with well-known anticancer drugs, such as aspirin, flavopiridol, mitomycin C, cisplatin, adriamycin, and DOX, and could induce cell death in various cancer cells [ 24 , 52 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sensitizing effect involves increased apoptosis and the enhancement of doxorubicin-induced G 2 cell cycle arrest (Catalano et al, 2006). In line with these findings, it has recently been reported that VPA, in combination with the highest concentration of doxorubicin that does not induce KAT-18 cell death, efficiently induced apoptosis in KAT-18 cells (Kim et al, 2009).…”
Section: Histone Deacetylase Inhibitorsmentioning
confidence: 90%
“…Although DOX, as well as sorafenib, were shown to cause cell death, partially by enhancing apoptosis in HCC cells [3,4,29], the exact mechanism underlying the pharmacological synergy has not yet been determined. Moreover, VPA was reported to sensitize anaplastic thyroid carcinoma (ATC) cells to DOX, which caused apoptosis via the induction of histone hyperacetylation or apoptosis-related gene expression [30][31][32]. Concurrently, several studies demonstrated that VPA showed synergistic effects with well-known anticancer drugs, such as aspirin, flavopiridol, mitomycin C, cisplatin, adriamycin, and DOX, and could induce cell death in various cancer cells [19,30,33,34].…”
Section: Discussionmentioning
confidence: 99%